Fish demand in Egypt: An analysis using Almost Ideal Demand System (AIDS) - Al-Mahish, Mohammed; Abd El-Radi, Hanady; Mursi, Hafsa (Indian Journal of Fisheries, 2021)
Egypt has a vast water area of about 13 million acres, and the amount of fish production capacity reached 1.82 million t in 2017. This represents an increase by 6.8% compared with 2016; however, the increase in population growth rate has caused a shortage in meeting consumers’ needs by about 15.47%. This research aims at estimating demand elasticity for Tilapia, Bayad, and Catfish in Egypt as they are the most important fish items prevalent in the Nile River. The results show that the demand for fish in Egypt is price inelastic. This means that price changes have a small impact on the quantity demanded of fish. In addition, tilapia was identified as a necessary fish item in Egypt. The Hicksian cross-price elasticities identified tilapia and bayad as substitutes for catfish.Keywords: Almost Ideal Demand System, Demand elasticity, Fish demand